Mechanisms behind the high mortality rate in chronic Chagas cardiomyopathy: unmasking a three-headed monster - Echeverría, Luis Eduardo; Serrano-García, Angie Yarlady; Rojas, Lyda Z.; Berrios-Bárcenas, Enrique A.; Gómez-Mesa, Juan Esteban; Gómez Ochoa, Sergio Alejandro (European journal of heart failure, 2024)
Chagas disease is a neglected tropical disease caused by the parasite Trypanosoma cruzi. Chronic Chagas cardiomyopathy (CCC), the most severe form of target organ involvement in Chagas disease, is characterized by a complex pathophysiology and a unique phenotype that differentiates it from other cardiomyopathies, highlighting its worse prognosis compared to other aetiologies of heart failure. The three pathophysiological mechanisms with the largest impact on this differential mortality include rapidly progressive heart failure, a high incidence of stroke, and a high burden of ventricular arrhythmias. However, despite significant advances in understanding the unique molecular circuits underlying these mechanisms, the new knowledge acquired has not been efficiently translated into specific diagnostic and therapeutic approaches for this unique cardiomyopathy. The lack of dedicated clinical trials and the limited CCC-specific risk stratification tools available are evidence of this reality. This review aims to provide an updated perspective of the evidence and pathophysiological mechanisms associated with the higher mortality observed in CCC compared to other cardiomyopathies and highlight opportunities in the diagnostic and therapeutic approaches of the disease.